The key that swallowed Joey Pigza - Gantos, Jack (Square Fish, 2015)
When both his parents go AWOL, young Joey Pigza is forced to become like a dad to his months-old baby brother, Carter Junior. Hilarity ensues as he tries, even with the help of a friend, until the real man of the house returns and Joey sees a ray of hope for fixing his family.